Recomendação de linhagens de feijão-caupi quanto à produtividade e escurecimento dos grãos para região semiárida - Araújo, Linda Brenna Ribeiro (2022)
The area cultivated with cowpea (Vigna unguiculata L. Walp.) and its production have grown in Brazil. However, the reality of the culture is still low yields, especially in the Brazilian Northeast, its main producing region. In addition, post-harvest problems are also observed in the crop, such as grain browning. Thus, the objectives of this work are to evaluate the genotype X environment interaction and grain browning under storage and to recommend, for the semiarid region of Ceará, productive, stable cowpea genotypes adapted to different cropping systems (rainfed and irrigated) and with reduced grain browning. In Chapter I, fourteen cowpea genotypes were evaluated in Value of Cultivation and Use (VCU) trials in six different cities in the state of Ceará (Crato, Pentecoste, Crateús, Madalena, Bela Cruz and Limoeiro do Norte). The experimental design used was randomized blocks, with four replications. Individual and joint analyzes of variance were performed and the means were grouped according to Scott-Knott. In order to make an efficient recommendation, the GGE biplot methodology was used to evaluate the adaptability and stability of the genotypes. The luminosity (L*) of the best performing genotypes was also evaluated. Genotype 9 (Pingo-de-ouro 1-5-8) was recommended for the state of Ceará for its stability in grain yield. Genotypes 1, 4, 8 and 10 were the most adapted to irrigated environments and genotypes 1, 2, 7 and 9 to rainfed areas. Genotype 1 (Bico-de-ouro 1-5-11) showed the lowest browning under storage. In Chapter II, the browning of the grains was also evaluated under different storage times, in a simple factorial scheme (15 genotypes x 5 periods – 0, 2, 4, 6 and 8 months), and the lightness variables (L*) were analyzed by the method of exclusive specular reflection, total extractable polyphenols (POL) and peroxidase (PER) and polyphenoloxidase (PPO) enzymatic activity, obtained byreading the respective extracts in a microplate spectrophotometer. The genotype that darkened the least was 15 (Setentão), which can be recommended for more demanding markets in terms of loss of luminosity over time. The mulatto genotypes showed a greater tendency to darken, while the white tegument did not darken over the evaluated time.